Divergent features of ERβ isoforms in triple negative breast cancer: progress and implications for further research - Yan, Shunchao; Wang, Jinpeng; Chen, Hong; Zhang, Duo; Imam, Murshid (Frontiers in Cell and Developmental Biology, 2023)
Estrogen receptor β (ERβ) was discovered more than 20 years ago. However, the extent and role of ERβ expression in breast cancer remain controversial, especially in the context of triple-negative breast cancer (TNBC). ERβ exists as multiple isoforms, and a series of studies has revealed an inconsistent role of ERβ isoforms in TNBC. Our recent results demonstrated contrasting functions of ERβ1 and ERβ2/β5 in TNBC. Additional research should be conducted to explore the functions of individual ERβ isoforms and develop targeted drugs according to the relevant mechanisms. Consequently, a systematic review of ERβ isoforms is necessary. In this review, we overview the structure of ERβ isoforms and detail what is known about the function of ERβ isoforms in normal mammary tissue and breast cancer. Moreover, this review highlights the divergent features of ERβ isoforms in TNBC. This review also provides insights into the implications of targeting ERβ isoforms for clinical treatment. In conclusion, this review provides a framework delineating the role and mechanisms of different ERβ isoforms in TNBC and sheds light on future directions for basic and clinical research.